The Influence of Self-Efficacy on Entrepreneurial Intention (A Study on University Students in Bandung City) - Rahmawati, Anisa; Solihat, Asri; Mubarok, Teten Mohammad Sapril (Entrepreneurship Faculty, Universitas Garut, 2025)
The high level of unemployment has required various parties to try to foster an entrepreneurial spirit in the community, especially university students. One way to overcome the problem of unemployment and improve the Indonesian economy is to increase the spirit of entrepreneurship and increase individual confidence in facing all the obstacles that occur to becoming an entrepreneur. In addition, entrepreneurship programs are expected to improve the Indonesian economy and create young entrepreneurs with undergraduate backgrounds that can help the government reduce unemployment. This study aimed to determine self-efficacy's effect on entrepreneurial intentions among students in Bandung City. This study is intended to examine the impact of self-efficacy on entrepreneurial intentions. This study's population was students pursuing undergraduate education in Bandung City. This type of research is quantitative research with a descriptive approach. The sample used in this study was 400 respondents distributed via Google Forms and then processed using SPSS statistics 26 using a purposive sampling technique. The analytical tools used in this study are classical assumption tests, simple linear regression, and hypothesis testing. The results stated that the self-efficacy variable has a positive and significant effect of 63% on entrepreneurial intention. While the remaining 37% is influenced by other variables not mentioned in this research model.